Analysis of the Key and Difficult Points in the Engineering Construction Technology of the Steel Structures of a Super High-rise Building - Dou, Lijun; Li, Hengxu (IOP conference series. Materials Science and Engineering, 2017)
In recent years, with the rapid development of the economy of China, the traditional building structure has not been able to meet the current people's demands and the super high-rise building has become a symbol of a city. In the current period, the research on the super high-rise building in the architectural industry of China is late and the technical blanks exist in some construction difficulties in the super high-rise steel structures. Based on the above, a brief analysis and discussion on the difficult construction technology in the steel structures of a super high-rise building and some measures are presented for reference of the relevant personnel in this paper.